Chapter The territorial organization of the Amalfi Coast: nature and man's intervention - Russo, Maria (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Amalfi Coast is characterized by jagged mountain ridges and valleys that include streams and plunges into the sea with steep cliffs, here and there interrupted by short sandy coasts. The coastal and inland towns contribute to the beauty of the landscape, rich in historical and artistic evidence from the Middle Ages. At the same time, urban agglomerations expanded, almost unique examples of adaptation to difficult environmental conditions. The study aims to analyze the natural and anthropogenic components of the whole, today.